2016
DOI: 10.1021/acsami.5b12382
|View full text |Cite
|
Sign up to set email alerts
|

Microphase-Separated PE/PEO Thin Films Prepared by Plasma-Assisted Vapor Phase Deposition

Abstract: Immiscible polymer blends tend to undergo phase separation with the formation of nanoscale architecture which can be used in a variety of applications. Different wet-chemistry techniques already exist to fix the resultant polymeric structure in predictable manner. In this work, an all-dry and plasma-based strategy is proposed to fabricate thin films of microphase-separated polyolefin/polyether blends. This is achieved by directing (-CH2-)100 and (-CH2-CH2-O-)25 oligomer fluxes produced by vacuum thermal decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The chemical composition of the ppPEO films and ppAA NPs was analyzed by XPS (Figure and Table ). Similar to the earlier findings, ppPEO is able to retain the ether groups of the original PEO structure, and the ether group content reaches 78 at.% for these specific conditions (Figure a). Smaller contribution from the C–C– and the C═O‐based groups is related to the formation of cross‐links and insignificant chemical transformations that occur during the plasma polymerization process.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The chemical composition of the ppPEO films and ppAA NPs was analyzed by XPS (Figure and Table ). Similar to the earlier findings, ppPEO is able to retain the ether groups of the original PEO structure, and the ether group content reaches 78 at.% for these specific conditions (Figure a). Smaller contribution from the C–C– and the C═O‐based groups is related to the formation of cross‐links and insignificant chemical transformations that occur during the plasma polymerization process.…”
Section: Resultssupporting
confidence: 90%
“…In the plasma polymerization community, microscale patterning was done typically by the sequential deposition of two different films using a mask . Our group has also shown that plasma copolymers demonstrating nanoscale phase separation can be produced by the plasma‐assisted vapor‐phase codeposition of two immiscible polymers . The method takes advantage of the ability of certain polymers to decompose thermally under vacuum, which releases oligomers .…”
Section: Introductionmentioning
confidence: 99%
“…Plasma polymerization from a thermally degraded solid polymer (plasma-assisted vacuum thermal evaporation) is most directly related to classical Physical Vapour Deposition (PVD) processes, but it utilizes plasma in the second step of the process. Long fragments of partially thermally decomposed bulk polymer fly through low-pressure plasma and they form a plasma polymer [9][10][11][12][13]. This method is able to produce thin films with relatively easily controllable cross-linking degree, as was demonstrated e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Most often, PLA is synthetised by polycondensation of D-or Llactic acid or from ring opening polymerization of lactide, a cyclic dimer of lactic acid [3], however other synthetic methods have been also studied [4][5][6]. Lowtemperature plasma based methods have proven to be very effective for fabrication of ultrathin, pinhole-free, polymeric and nanocomposite coatings [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation